Intrapartum Fetal Heart Rate: A Possible Predictor of Neonatal Acidemia and APGAR Score - Medeiros, Thâmila Kamila de Souza; Dobre, Mirela; da Silva, Daniela Monteiro Baptista; Brateanu, Andrei; Baltatu, Ovidiu Constantin; Campos, Luciana Aparecida (Frontiers in Physiology, 2018)
Background: Predicting perinatal outcomes based on patterns of fetal heart rate (FHR) remains a challenge. The aim of this study was to evaluate intrapartum FHR variability as predictor for neonatal acidemia and APGAR score. Methods: This was a retrospective observational study of 552 childbirths. Multivariable linear regression models were used to assess the association between FHR variability and each of the following outcomes: arterial cord blood pH and base deficit, Apgar 1, and 5 scores. Variables used for adjustment were maternal age, comorbidities (gestational diabetes, preeclampsia, maternal fever, and hypertension), parity, gravidity, uterine contractions, and newborn gestational age, and weight at birth. Results: The following factors were associated with an increased risk of metabolic acidosis and low Apgar scores at birth: increased mean and coefficient of variation (CV) of the FHR, type of delivery and decreased parity. Each 10-beat/min increase in the FHR was associated with an increase of 0.43 mEq/L in the base deficit, and a decrease of 0.01 in the pH, 0.2 in the Apgar 1, and 0.14 in the Apgar 5 scores. Each 10% increase in the CV of the FHR was associated with an increase of 4.05 mEq/L in the base deficit and a decrease of 0.13 in the pH, 1.31 in the Apgar 1, and 0.86 in the Apgar 5 scores. Conclusion: These data suggest the intrapartum FHR variability is physiologically relevant and can be used for predicting the acidemia and Apgar scores at birth of the newborn infants without severe cases of morbidity and from uncomplicated pregnancies.